Role of Innovative Entrepreneurship Education on Entrepreneurial Intention among STEM Students at a Rural University - Nobathembu Faleni; Arthur Mapanga (Research Synergy Foundation, 2026)
This study examines the effect of entrepreneurship education on the entrepreneurial intentions of STEM students at a historically disadvantaged university in South Africa, addressing a critical research gap: limited evidence on how targeted interventions influence entrepreneurial aspirations in emerging economies. A mixed-methods design was employed, with 285 students completing a customized Entrepreneurial Intention Questionnaire (EIQ) before and after two interventions: a traditional classroom module and a work-integrated learning (WIL) component. Quantitative data were analyzed using descriptive statistics and repeated-measures ANOVA, while qualitative insights were derived from semi-structured interviews and thematic analysis using NVivo software. The results revealed significant positive shifts across the six constructs of entrepreneurial intention, with WIL having the most potent effect on perceived feasibility and self-efficacy. Qualitative findings highlighted mindset transformation, enhanced confidence, peer collaboration, real-world application, and mentorship as key factors. Based on these insights, this study recommends integrating experiential learning, mentorship, and tailored curricula to strengthen STEM students' entrepreneurial competence. These findings offer actionable guidance for educators and policymakers seeking to design entrepreneurship education programs that foster innovation and economic resilience in marginalized contexts.